Profil Keterampilan Belajar Mahasiswa pada Perkuliahan Teknik Laboratorium Konseling - Folastri, Sisca; Rangka, Itsar Bolo; Rahmaniah, Ayu (Jurnal Fokus Konseling, 2018)
Counseling skills are one of the component skills that should be possessed by the prospective counselor who studied in college. It requires learning skills sufficient for students to succeed in mastering the skills of counseling. This research aims to look at the description of the learning skills of the students in laboratory techniques and associated counseling. This research using a sample survey method in this research as much as 61 students and active learning in the semester V and took an engineering laboratory course counseling. The analysis of the data using simple statistical analysis. The results showed that the picture quality of students learning skills is at a high of 90.16% category.